The 2010 International Joint Conference on Neural Networks (IJCNN) 2010
DOI: 10.1109/ijcnn.2010.5596602
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning approach for crude oil price prediction with Artificial Neural Networks-Quantitative (ANN-Q) model

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 10 publications
1
31
0
Order By: Relevance
“…Price of Crude Oil Researchers such as Abdullah in 2010 [12], Kantaporn et al [13], Arshad et al [10] confirmed the relationship between price of crude oil and CPO. Razak et al [14]employed the EngleGranger co-integration test to demonstrate a significant long term correlation between CPO price and crude oil price which was consistent with the recent work of Appalanaidu [15].…”
Section: Factors Influencing Cpo Pricementioning
confidence: 99%
“…Price of Crude Oil Researchers such as Abdullah in 2010 [12], Kantaporn et al [13], Arshad et al [10] confirmed the relationship between price of crude oil and CPO. Razak et al [14]employed the EngleGranger co-integration test to demonstrate a significant long term correlation between CPO price and crude oil price which was consistent with the recent work of Appalanaidu [15].…”
Section: Factors Influencing Cpo Pricementioning
confidence: 99%
“…It is important to analyses the probabilistic assumption of oil prices in terms of normality, linearity and serial correlation [4]. To forecast crude oil prices, a variety of approaches have been proposed by numerous authors employing time series [5][6][7][8][9][10], financial models [11,12] and structural models [13][14][15][16][17][18].…”
Section: Econometric Modelsmentioning
confidence: 99%
“…The study identifies that historical oil prices (either daily, weekly or yearly) are the most popular input variables used by researchers. Abdullah [18] has used 22 input variables from the categories as mentioned in Table 3 to achieve high prediction accuracy but the variables were selected on judgemental criteria. To handle optimal long-term oil price forecasting, Azadeh et al [64] developed a flexible algorithm based on artificial neural networks and fuzzy regression by using oil supply, crude oil distillation capacity, oil consumption of Non-OECD, USA refinery capacity and surplus capacity as economic indicators.…”
Section: Covers This In Detail) There Is No Solitary Indicatormentioning
confidence: 99%
See 1 more Smart Citation
“…SampEn is even less sensitivity to the length of data sets and provides more consistent results which being also reliable to be used in small data sets (Chen et al, 2006;Ferrario et al, 2006;Lake et al, 2002;Yentes et al, 2013). It is important to note that ApEn and SampEn have also been used as a metric to evidence the chaotic behaviour of time series that presents positive λ (Cencini and Ginelli, 2013;Chen et al, 2016;Gaspard et al, 1998;Kaplan et al, 1991;Pincus, 1995;Sanei, 2013;Schreiber and Kantz, 1995) The chaotic behaviour of the price sequence of several mineral commodities has been assessed previously, however these studies (Abdullah and Zeng, 2010;He et al, 2015;Panas, 2001;Panas and Ninni, 2000) have been limited to sample periods of 15 years or less, and used daily or monthly prices. It is important to verify the time-related behaviour of mineral commodity prices in the longterm by using annual data, due to the impact of economic decisions, technological and regulatory changes which can be observed over years (Bernanke, 2013;Slade, 2015;Yellen, 2013).…”
Section: Introductionmentioning
confidence: 98%